2007
DOI: 10.1200/jco.2007.10.9777
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Clinical Oncology Clinical Evidence Review on the Ongoing Care of Adult Cancer Survivors: Cardiac and Pulmonary Late Effects

Abstract: An increased incidence of cardiac and/or pulmonary dysfunction is observed in cancer survivors. Research is needed to identify high-risk patients, and to determine the optimal screening strategies and subsequent treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
504
0
26

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 710 publications
(534 citation statements)
references
References 105 publications
4
504
0
26
Order By: Relevance
“…It manifests in several forms, ranging from acute arrhythmias and nonspecific electrocardiogram changes to decreases in LVEF. Beside age, hypertension, diabetes and coronary heart disease, trastuzumab treatment represents a significant risk factor for the development of anthracycline related cardiotoxicity [12,18]. The most severe complication is cardiomyopathy leading potentially to a permanent cardiac damage [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It manifests in several forms, ranging from acute arrhythmias and nonspecific electrocardiogram changes to decreases in LVEF. Beside age, hypertension, diabetes and coronary heart disease, trastuzumab treatment represents a significant risk factor for the development of anthracycline related cardiotoxicity [12,18]. The most severe complication is cardiomyopathy leading potentially to a permanent cardiac damage [20].…”
Section: Discussionmentioning
confidence: 99%
“…This risk appears to be higher in patients receiving concurrent anthracyclines [29]. Slamon et al [12] 123 [30]. However, natural history of trastuzumab related cardiotoxicity differs significantly from the anthracycline induced one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Recently, a large review of literature on the retrospective study performed and the surveillance of adult cancer survivors were presented with special focus on cardiac and pulmonary side effects. 24 The review concluded that the incidence of radiotherapy-induced cardiac side effects was in the range of 10-30%. The panel also concluded that very few prospective studies have been performed that investigates the advantage of surveillance in HL survivors.…”
Section: Discussionmentioning
confidence: 99%
“…They expressed a need for more prospective studies of cardiovascular prevention. 24 Diabetes mellitus, hypertension, hypercholesterolemia, first degree relative with CVD, history of antracycline therapy, obesity, physical inactivity and smoking are likely to act in concert with radiotherapy to the heart, coronary arteries and carotid arteries. These factors might increase risk of CVD in this patient cohort.…”
Section: Discussionmentioning
confidence: 99%